Marriage Law in the Legal System of Jordan and South Yemen - Asrofi; Oyo Sunaryo Mukhlas (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Family law in various Muslim countries of the world in its application and implementation is adjusted to the region or country of origin and depends on the policy of the government itself. Muslim countries have different legal provisions for their implementation, as do Jordan and South Yemen, both Muslim countries are very interesting to examine and analyze. The development of Islamic family law (al-Ahwal al-Shakhshiyah) in the modern Islamic state can be said to be a new format that accommodates the ideas of renewal of Islamic Legal thought. This research uses library research methods. In this study, the author used a qualitative research approach using a descriptive method of analysis. The results of this study that family law carried out in Jordan are among others related to the issue of marriage age, marriage vows, interfaith marriage, marriage registration, divorce and polygamy. Family law reform in Jordan has implemented various universal provisions of basic values in Islam by considering aspects of maslahah. Family law in South Yemen belongs to a group of countries that follow (enforce) traditional Islamic family law, where classical Islamic family law is applied according to various schools of thought as inheritance that is hereditary, unchanged and not codified until today. The state of Yemen applies the Shafi'i sect and the Hanafi sect in addition to the Zaydi Shi'a sect.